PENGARUH KEPEMIMPINAN DAN DISIPLIN TERHADAP PRODUKTIVITAS PEGAWAI KANTOR DESA SALO PALAI MUARA BADAK - Akhmadiansyah; Sulistina, Eka; Johansyah (I-Con Media, 2023)
The Influence of Leadership and Discipline on Work Productivity of the employees of the Salok Palai Muara Badak Village office, The main task of the government is to carry out sub-district duties and carry out other tasks based on applicable regulations. The government of the Salo Palai Muara Badak Village Office, which works in community service, should provide the best service to the community. The purpose of this study was to determine the simultaneous and partial effect of leadership and discipline variables on the work productivity of the employees of the Salok Palai Muara Badak village office. The number of samples in this study found 18 employees at the village office of salok palai. Analysis of this study using multiple regression analysis with the help of SPSS. The research results obtained are that there is a simultaneous and significant influence between improvement and discipline on employee work productivity at the Salok Palai Muara Badak Village Office, there is a partial influence between leadership variables on employee productivity at the Salok Palai Muara Badak Village Office and partial influence between variables discipline towards the productivity of the employees of the Salok Palai Muara Badak Village Office.